2019
DOI: 10.1111/boc.201900014
|View full text |Cite
|
Sign up to set email alerts
|

Dock5 is a new regulator of microtubule dynamic instability in osteoclasts

Abstract: Background Information. Osteoclast resorption is dependent on a podosome-rich structure called sealing zone. It tightly attaches the osteoclast to the bone creating a favourable acidic microenvironment for bone degradation. This adhesion structure needs to be stabilised by microtubules whose acetylation is maintained by down-regulation of deacetylase HDAC6 and/or of microtubule destabilising kinase GSK3β activities. We already established that Dock5 is a guanine nucleotide exchange factor for Rac1. As a conseq… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 54 publications
2
17
0
Order By: Relevance
“…Previously, it has been shown that the Golgi and/or microtubules play an important role in cardiomyocyte cell growth (hypertrophy) ( Nash et al, 2019 ) and bone resorption activity of osteoclast ( Guimbal et al, 2019 ; Ng et al, 2013 ; Ye et al, 2011 ). Therefore, we tested whether AKAP6 is required for these cellular functions.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, it has been shown that the Golgi and/or microtubules play an important role in cardiomyocyte cell growth (hypertrophy) ( Nash et al, 2019 ) and bone resorption activity of osteoclast ( Guimbal et al, 2019 ; Ng et al, 2013 ; Ye et al, 2011 ). Therefore, we tested whether AKAP6 is required for these cellular functions.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, Arap1 couples the regulation of actin through its RhoA GAP domain to that of membrane trafficking to the ruffled border through its Arf GAP domain (Segeletz et al, 2018). Similarly, Dock5 is likely to participate in actin and microtubule crosstalk as this GEF for Rac also controls microtubule dynamics and acetylation in osteoclasts (Guimbal et al, 2019), as detailed below.…”
Section: The Regulation Of Actin Dynamics In Osteoclasts and Impact Omentioning
confidence: 99%
“…2). In the absence of DOCK5, GSK3β activity increases and microtubules acetylation is reduced, with a concomitant reduction in the length and duration of microtubule growth (Guimbal et al, 2019).…”
Section: Actin and Microtubule Crosstalk At The Podosome Beltmentioning
confidence: 99%
“…These results speculated that Rac1 and Rac2 might function in osteoclastic organelle actin dynamics regulating, such as: actin filament ends and podosomes. In fact, Rac1 and Rac2 proteins have overlapping roles in podosome assembly and SZL formation by localizing Arp2/3 at podosome sites during osteoclastogenesis [7,[21][22][23][24][25][26][27]. Osteoclasts generated from the Rac1 and Rac2 double knockout mouse are devoid of podosomes and SZ, which finally showed impaired bone resorption capacities [24,[28][29][30][31][32].…”
Section: Rac Isoforms (Rac1 and Rac2) In Regulation Of Cytoskeletal Amentioning
confidence: 99%